2019
DOI: 10.2188/jea.je20170283
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Maternal Age at the First Childbirth on Gestational Age and Birth Weight: The Japan Environment and Children’s Study (JECS)

Abstract: Background: In Japan, mean maternal age at first childbirth is increasing. The aim of this study was to investigate whether maternal age at the first childbirth is a risk factor for preterm birth (PTB), low birth weight (LBW), and small for gestational age (SGA). Methods: We used the results of Japan Environment and Children's Study (JECS) who gave birth in 2011-2014. Cases of primiparous singleton pregnancies where the subject was ≥20 years and delivered after 22 weeks were included. All subjects were categor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
65
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

6
3

Authors

Journals

citations
Cited by 60 publications
(67 citation statements)
references
References 25 publications
0
65
0
2
Order By: Relevance
“…Therefore, it might be reasonable to assume that systematic inflammation as a significant increase in WBCs in the proinflammatory diet group was related to PTB. However, PTB has the same endpoint, consisting of two clinical subtypes: spontaneous PTB and medically indicated PTB, which is conducted for cases of SGA or HDP (Kyozuka et al, ). Habitual proinflammatory diet has associations with regulation of inflammation, leading to modulation of the atherogenesis process and endothelial dysfunction (Barbaresko, Koch, Schulze, & Nöthlings, ).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it might be reasonable to assume that systematic inflammation as a significant increase in WBCs in the proinflammatory diet group was related to PTB. However, PTB has the same endpoint, consisting of two clinical subtypes: spontaneous PTB and medically indicated PTB, which is conducted for cases of SGA or HDP (Kyozuka et al, ). Habitual proinflammatory diet has associations with regulation of inflammation, leading to modulation of the atherogenesis process and endothelial dysfunction (Barbaresko, Koch, Schulze, & Nöthlings, ).…”
Section: Discussionmentioning
confidence: 99%
“…]30 years based on a previous study that showed that maternal age was related to certain obstetric outcomes, such as PTB, LBW, and SGA. 26 BMI before pregnancy was categorized into three groups (<18.5 kg/m 2 , 18.5-25.0 kg/m 2 , and >25.0 kg/m 2 ). 27,28 Parity was categorized into two groups (nulliparous and multiparous).…”
Section: Obstetric Outcomes and Confounding Factorsmentioning
confidence: 99%
“…]35 years). 22,23 BMI before pregnancy was categorized into three groups (<18.5, 18.5-25.0, and <25.0). Parity was categorized into two groups (nulliparous and multiparous).…”
Section: Obstetric Outcomes and Confounding Factorsmentioning
confidence: 99%